Consumer Behavior in the Era of Digital Transformation: A Global Research Perspective - Vicky Dzaky Cahaya Putra; Ifan Wicaksana Siregar (PT. INOVASI TEKNOLOGI KOMPUTER, 2026)
The objective of this study is to examine consumer behavior in the context of the digital era using a bibliometric methodology. The advent of the digital age has brought about a profound transformation in the manner in which customers engage with products, companies, and information. Within this particular context, the utilization of bibliometric research has emerged as a pertinent approach for discerning patterns, areas of research emphasis, influential contributors, and advancements pertaining to consumer behavior within the digital realm. This research methodology involves the acquisition of data from scholarly articles that are indexed in the Scopus database. The data is subsequently subjected to examination by bibliometric methods, including citation analysis, keyword analysis, and data visualization employing VOS Viewer. The anticipated outcomes of this investigation are poised to unveil evolutionary patterns in consumer behavior research within the context of the digital era, ascertain the most often discussed topics, and identify the principal contributors within this domain. The results obtained from this research can offer significant contributions to scholars, professionals in the business sector, and legislators in understanding the most recent advancements in consumer behavior inside the digital realm. The anticipated outcomes of this study are likely to contribute to an enhanced comprehension of the transformation in consumer contact within the digital era. Furthermore, these findings are predicted to have significant strategic consequences for businesses and marketing practices in this dynamic and evolving landscape